A meta-analytical umbrella review assessing urban environment exposures and cognitive health outcomes. - Glover, Sophie; Cleland, Claire; Trott, Mike; Akaraci, Selin; O'Kane, Niamh; Valson, Joanna; McGuinness, Bernadette; Hunter, Ruth (Age & Ageing, 2026)
Introduction Global population ageing is increasing the burden of cognitive decline and dementia. While systematic reviews have examined links between environmental exposures and cognitive outcomes, evidence remains fragmented. This umbrella review aimed to synthesise and meta-analyse systematic reviews on urban environmental exposures and cognitive health. Methods A meta-analytic umbrella review (PROSPERO: CRD42023425117) was conducted using PubMed, Embase and PsycINFO. Systematic reviews examining urban environments and cognitive health were included. Methodological quality was assessed using the Joanna Briggs Institute tool. Meta-analytic evidence was graded ('convincing' to 'not significant') based on sample size, effect strength and bias. Narrative synthesis was also performed. Results From 6391 records, 54 systematic reviews were included, comprising 66 meta-analysed outcomes and 270 exposure–outcome associations. Air pollution showed the strongest evidence: particulate matter 2.5 (PM2.5) (10/11 significant outcomes) and nitrogen dioxide/nitrogen oxide (5/10) demonstrated highly probable detrimental effects on cognitive health. Social relationships (5/8) showed probable beneficial effects. Green and blue spaces were associated with reduced dementia risk (3/6). Narrative findings supported these results and identified research gaps, particularly for travel behaviour (no outcomes identified). Conclusion There is highly probable evidence linking air pollution to poorer cognitive health and probable evidence supporting social relationships. Further research is needed on urban design, noise, light exposure and underexplored pollutants (CO, SO₂). Policies should prioritise reducing air pollution and promoting social engagement to support cognitive health and dementia prevention.